Using the Canva Application as an Arabic Learning Media at SMA Plus Panyabungan - Adam Mudinillah; M. Rizaldi (P3M IAI Nusantara Batang Hari, 2021)
The purpose of this research article or journal is to describe the benefits of using the Canva application to increase the effectiveness of students' learning in Arabic learning. The research of this article is a qualitative research using a library research approach (library study). The research location is SMA Plus Panyabungan. The literature sources for this article are journals and books that are similar or similar to this research. The discussion of this article is about and the benefits of using the Canva application as an Arabic language education medium at the SMA/MA level. The result of this research is that the Canva application is a very helpful medium for teachers and students in the educational process such as making the power pont more attractive to display. The Canva application increases the creativity of teachers or students in Arabic education, especially in mastering Arabic vocabulary or what is called mufrodat. The Canva application is also useful for increasing students' interest in learning so that the learning process is not boring and interesting as well as fun.